A study on the relationship between building teamwork and employees' performance at axa partners, asia assistance network, Selangor / Nurrinna Zubir - Zubir, Nurrinna (Faculty of Business and Management, 2020)
The purpose of this paper is to investigate the relationship between the factors of building teamwork towards employee's performance in AXA Partners, Asia Assistance Network at Petaling Jaya, Selangor. A total of86 sets of questionnaires were distributed to the employees at AXA Partners, Asia Assistance Network by using cluster sampling. The response rate in this study was 100 percent. Based on the research finding from the demographic section, the result was stated that the majority of respondents were a male employee at AXA Partners, Asia Assistance Network and the majority who has answered the questionnaire was between 26 to 30 years old. Furthermore, the finding stated that the majority of the respondents were married and the race was Chinese. It was also resulted that majority of respondents' monthly income was between RM 3,001 to RM 4,000 who were majority working with the company within 1 year to 2 years. It is also found that the factors of building teamwork have a positive relationship with employee's performance since all the four hypothesis have been accepted. In this study, the researcher has suggested employees to build more positive relationship among colleagues to improve their cohesiveness when working in team. It is also suggested to company to provide a teamwork training to the employee and to improve leadership skill to increase the level of teamwork among employees. As conclusion, this paper has revealed the importance of building teamwork at the company would increase the employees' performance.